Comparing the Pattern of Lower Limb Joints Coordination in an Optional and Selective Sprint Start of Elite Women Runners - Zahra Bahadori; Moein Koohestani; Heydar Sadeghi (Biyumikānīk-i varzishī)
Objective: The sprint start is a complex skill characterized by a multi-joint and multi-plane task requiring complex muscle coordination to reach a large force exerted in the horizontal direction in a short time. Previous studies indicated that efficient acceleration over the first portion of a race is influenced by how a sprinter is positioned in the set command blocks. Methods: A total of 15 elite women runners participated in this study. The subjects performed three optional, and five selected sprint starts with 2-minute intervals. The Noraxon-MyoMotion device collected the kinematic data, and a continuous relative phase method was used to calculate the joint coordination pattern. Results: The pattern of coordination between the lower limb joints were divided into 10 phases. There were differences between the two types of starters in the initial phases, but no difference was noticed from the fourth phase. Conclusion: Indeed, there was irregularity in the early phases of the selected start type, while in the following phases, the coordination pattern coincided, and it seems that if this process does not affect the speed and acceleration of the athlete, it can be cautiously noted that sitting in any way in the start technique will ultimately create common coordination in the joints.